Optimization and economic analysis of textile wastewater treatment by photo-fenton process under artificial and simulated solar radiation - Carmen S. D. Rodrigues (2013)
The degradation via the photo-Fenton process of dyes and organic compounds present in acrylic, cotton, and polyester dyeing wastewaters was investigated, aiming at reducing the consumption of chemicals, as compared to the dark Fenton process, while simultaneously minimizing the energy costs by using simulated solar radiation. The reduction of the hydrogen peroxide dose is limited by the need of achieving treated effluents complying with discharge limits, but for dark Fenton the operating costs are excessive. The costs associated with the use of artificial radiation in the photo-Fenton process (17.4, 9.6, and 2.9 epsilon/m(3) for acrylic, cotton, and polyester effluents, respectively) are also too high. The use of (simulated) solar light allows for obtaining high degrees of removal of color (> 98-99%) and significant COD (30.1-72.0%) and DOC (46.2-71.5%) reductions at a total cost reduction of a factor of ca. 3. Treated effluents by the solar photo-Fenton process also meet the discharge standards.